The Effect of Using TikTok on Z Generation Etiquette - Aisyah Ichsani Maulida; Pitri Noviyanti; Wahyunengsih Wahyunengsih (Da'wa Faculty of Islamic State University Salatiga, 2022)
Social media has many uses, ranging from creating video content, and spreading information or news, to even making money. However, ticktock use may also have a negative effect on the user if not used wisely, such as a TikTok application used by teens to judge content they do not like. Hence the often effect that comes upon adolescents especially the z generation is their change of ethics in real life. The purpose of this study is to know the effect that TikTok use has on 2022 journalistic and non-sense that there is or will not be the effect that online personality ticktock usage has on its real life. This research is done using qualitative methods, where it employs analysis or conclusion by combining and collecting data. The result is that some 2022 journalistic students are affected by the excessive use of TikTok which has an impact on their ethics in real life from speaking, lifestyle, and so on. And based on our research, it can be concluded that the use of a TikTok application has indeed had some negative effects on one of the many ethical changes in youth, especially the Z generation. The most frequent change is laziness in any case and the shaping of a lifestyle.